ANALYSIS ON THE INFLUENCE OF EXECUTIVE COMPENSATION, GOOD CORPORATE GOVERNANCE AND FREE CASH FLOW ON INCOME SMOOTHING PRACTICE - Bellasari, Kris (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2018)
A quantitative study was conducted to examine the effect of executive compensation, good corporate governance (GCG), and free cash flow (FCF) on income smoothing, either respectively or simultaneously. By exercising 13 companies, partially from year 2008, 2009, 2012, 2015, and 2016, there are merely four non-smoothers out from 28 total samples. By using multi-linear regression model, the results show that executive compensation and GCG has no significant influence on income smoothing respectively whereas FCF is positively related to the income smoothing. However, these independent variables have a significant effect on the income smoothing practice simultaneously.Â Keywords: agency problem, executive compensation, good corporate governance (GCG), free cash flow (FCF), income smoothing